Inland [compact disc, unabridged] : a novel - Obreht, Téa (Random House Audio, 2019)
In the lawless, drought-ridden lands of the Arizona Territory in 1893, two extraordinary lives collide. Nora is an unflinching frontierswoman awaiting the return of the men in her life, her husband, a newspaperman, who has gone in search of water for the parched household, and her elder sons who have vanished after an explosive argument. Nora is biding her time with her youngest son, who is convinced that a mysterious beast is stalking the land around their home, and her husband's seventeen-year-old cousin, who communes with spirits. Lurie is a former outlaw and a man haunted by ghosts. He sees lost souls who want something from him, and he finds reprieve from their longing in an unexpected relationship that inspires a momentous expedition across the West.